2012
DOI: 10.4236/ojped.2012.21004
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus and adenovirus in acute lower respiratory infections in hospitalized infants and children

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…This greater severity of mixed RSV‐adenovirus infections compared to single RSV infections was suggested by a previous study in hospitalized infants, which reported that mixed viral infections (of which a significant proportion had mixed RSV‐adenovirus infections) were associated with longer hospital stays compared to single RSV infections . Possible reasons for these variability in the reported outcome of mixed RSV‐adenovirus infections are differences in environmental, host (e.g., genetic immune response, previous immune condition, infected target cells), and viral factors (e.g., serotypes) . Another possible reason could be that adenovirus alone produces a more severe disease with no additional severity of a RSV infection.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This greater severity of mixed RSV‐adenovirus infections compared to single RSV infections was suggested by a previous study in hospitalized infants, which reported that mixed viral infections (of which a significant proportion had mixed RSV‐adenovirus infections) were associated with longer hospital stays compared to single RSV infections . Possible reasons for these variability in the reported outcome of mixed RSV‐adenovirus infections are differences in environmental, host (e.g., genetic immune response, previous immune condition, infected target cells), and viral factors (e.g., serotypes) . Another possible reason could be that adenovirus alone produces a more severe disease with no additional severity of a RSV infection.…”
Section: Discussionmentioning
confidence: 73%
“…Another possible reason could be that adenovirus alone produces a more severe disease with no additional severity of a RSV infection. Although this concept may be supported by the prominent effects of adenovirus on mononuclear cell activation and release of pro‐inflammatory cytokines compared to RSV, at the present time, there is no clear evidence demonstrating that adenovirus causes more severe respiratory disease in children than RSV …”
Section: Discussionmentioning
confidence: 88%
“…Another study of 9 RSV-confirmed infants found that 75% of children with RSV-ADV coinfection died despite mechanical ventilation [ 35 ]. Even though ADV alone may be responsible for more severe disease, clinical features such as hospital stay were not found to differ between RSV and ADV hospitalized LRTI [ 36 ]. However, increased pathogenicity may be explained by distinctly different immunological responses produced by RSV and ADV.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our previous findings showing that age less than 6 months, prematurity, congenital heart disease, and mixed RSV‐adenovirus infection were independent predictors of severe ALRI in a different population of patients, [Rodriguez et al, ] the present study identified different predictors of severe ALRI. Possible explanations for these discrepancies might be differences in environmental, host (e.g., genetic immune response, previous immune condition, infected target cells), and viral factors (e.g., serotypes) [Barberi et al, ].…”
Section: Discussionmentioning
confidence: 99%